[I092] Initial experience with the elekta unity system. (August 2018) - Thorwarth, Daniela
Abstract : In this presentation, a brief overview on the potential and also the challenges of online adaptive MR-guided radiotherapy (MRgRT) will be given. Moreover, the technical characteristics of the hybrid MR-Linac system Unity (Elekta AB, Stockholm, Sweden) will be discussed including implications for clinical workflows, dosimetry and treatment planning. General aspects related to MRgRT as well as specific issues with respect to the Elekta Unity system consisting of a 1.5 T MRI and a 7MV linear accelerator will be presented. Futhermore, first experiences, dosimetric characterisations and phantom/ patient data will be discussed.